Pengaruh Level Imbangan Karbon dan Nitrogen Dalam Ensilase Campuran Lelehanak (Mucuna sp) dengan Rumput Kume (Sorghum plumosum var. Timorense) Terhadap Kualitas Fisik - Banu, Selmi Rosanti; Kleden, Markus Miten; Mullik, Yelly M (Yayasan Sumber Daya Manusia Cerdas, 2025)
The purpose of this study was to determine the effect of the carbon-nitrogen balance in the ensiase mixture of lelehanak (Mucuna sp) and kume grass (Sorghum plumosum var. Timorense) on color, texture, scent and temperature. The method used in this study is an experimental method using a completely randomized design (CRD) with 3 treatments and 4 replications. The treatment was C-N20 = kume grass 387 gr + mucuna 4591 gr + rice bran 20 gr. C-N30 = kume grass 2115 gr + mucuna 2772 gr + rice bran 111 gr and C-N40 = kume grass 4057 gr + mucuna 728 gr + rice bran 213 gr. Data analysis with analysis of varians (ANOVA) and continued with Duncanʼs multiple distance test. The research carried out obtained average results for each texture treatment CN20= 2,50±0,61, CN30= 2,40±0,50, CN40= 2,20±0,41, the average color for each treatment was: CN20= 2,20±0,62, CN30= 2,90±0,31, CN40= 2,95±0,22, the average odor of each treatment was: CN20= 2,80±0,95, CN30= 2,85±0,75, CN40= 3,05±0,69, while the temperature (C˚) are: CN20= 30,88±0,86, CN30= 31,35±0,91, and CN40= 32,73±0,63. The results of the analysis of variance showed that the treatment had significant effect (P<0,05) on temperatur and color had no significant effect (P>0,05) on aroma and texture. From the results obtained, the general conversion of silage is in the criteria from good to very good. It can be concluded that the best level of carbon nitrogen balance is found in the CN40 balance.